Android mobile application for web-based digital asset management system - Lee, Kai Quan (2017)
AMPS (Asset Management and Production System) is a powerful web-based system that provides asset tracking and file hosting with synchronization services. This projects targets to have a mobile application as its extension to improve user enormously.